Jesus, Politics, and Society, A study of Luke’s Gospel - Pathrapankal, Joseph (Journal of Dharma, 1980)
Richard J. Cassidy, Jesus, Politics, and Society, A study of Luke’s Gospel, Maryknoll, N.Y.: Orbis Books, 1978, pp. x + 230, 7.9.